2017
DOI: 10.1177/0022034517695518
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 Channels Mediate Human Gingival Fibroblast Response to Phenytoin

Abstract: Drug-induced gingival enlargement (GE) is a frequent adverse effect observed in patients treated with anticonvulsant, immunosuppressant, and some antihypertensive medications-the antiepileptic phenytoin being the main drug associated with GE due to its high incidence (around 50%). The molecular mechanisms behind drug-induced gingival overgrowth are still unknown. By reverse transcription polymerase chain reaction, we demonstrate that the calcium-permeable ion channels TRPA1, TRPV1, and its capsaicin-insensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Gingival fibroblasts, the most abundant cellular type in periodontal tissue, play crucial role in GO 1,26 . In the present study, we showed that enhanced expression of KCNQ1 as well as increased outward K + currents was presented in gingival tissues derived from HGF patients.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Gingival fibroblasts, the most abundant cellular type in periodontal tissue, play crucial role in GO 1,26 . In the present study, we showed that enhanced expression of KCNQ1 as well as increased outward K + currents was presented in gingival tissues derived from HGF patients.…”
Section: Discussionsupporting
confidence: 58%
“…While extensive studies focused on intracellular Ca 2+ metabolism in DIGO, 26,27 our study firstly proposed that intracellular K + changes may be the cause of GO. Indeed, gain‐of‐function mutations in five potassium channel genes, KCNQ1 , KCNH1 , KCNJ8 , ABCC9 , and KCNK4 , were all strongly positively correlated with a GO phenotype in different syndromic diseases 7,8,10‐12 .…”
Section: Discussionmentioning
confidence: 92%
“…), and the activation of TRPA1 by phenytoin has been shown to increase the proliferation of human gingival fibroblasts (Lopez‐Gonzalez et al . ). Therefore, it was hypothesized that an alkaline pH stimulates channels and activates extracellular‐regulated kinase (ERK; phospho‐p44/42) in HCEM.…”
Section: Discussionmentioning
confidence: 97%
“…Endogenously, TRPV1 is opened mainly by high temperatures (>43°C), acidity, N ‐arachidonoyl dopamine, N ‐oleoyldopamine, and AEA . TRPV1 consists of a protein with six transmembrane domains and is found mainly in the nociceptive neurons of the peripheral nervous system, but has also been described in many other tissues, including gingival fibroblasts and periodontal ligament cells . TRPV1 is involved in the transmission and modulation of pain, is mainly permeable to Ca 2+ , and has been demonstrated to regulate vasodilatation, inflammatory response, and osteogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 TRPV1 consists of a protein with six transmembrane domains and is found mainly in the nociceptive neurons of the peripheral nervous system, but has also been described in many other tissues, including gingival fibroblasts and periodontal ligament cells. 17,18 TRPV1 is involved in the transmission and modulation of pain, is mainly permeable to Ca 2+ , and has been demonstrated to regulate vasodilatation, inflammatory response, and osteogenesis. 19,20 Moreover, both TRPV1 and TLR4 have been associated to distinct types of periodontal disease in a study of human tissue samples.…”
Section: Introductionmentioning
confidence: 99%